Los pjaros are feliz and are dreaming about gwiazdy: Facilitating Translingual Creative Writing in the Primary Classroom - Barbour, Catherine (My University, 2020)
Although one in five state-educated children in England speaks a language other than English at home, there is little space in the National Curriculum for the expression of this linguistic heritage. In this article we make the case for facilitating multilingualism in the primary classroom through translingual creative writing, which involves mixing two or more languages. We draw on empirical research with a class of lower Key Stage 2 children of diverse linguistic backgrounds and abilities at a school in south London. The pupils were set the task of writing a poem that combined English with other languages so that we could observe how they engaged with the process of translanguaging. We suggest that translingual writing exercises in the classroom provide a range of benefits, including the creation of a space for the valorisation of children’s cultural capital; the facilitation of valuable peer-teaching and collaboration; freedom to explore playfulness with language; and a chance to experiment with and reflect on creative writing processes.
PUBLISHED
Special Issue: Multilingualism and English Teaching ed. by Rachael Gilmour
Keywords: Translingualism; Translanguaging; Heritage Languages; Creative Writing; Key Stage 2; Identities in Transformation; Inclusive Society; Multilingual pedagogy; Education